Re-thinking Internet’s Regulability: From Lessig to IPv6 - Koniakou, Vasiliki (AoIR Selected Papers of Internet Research, 2016)
The wide dissemination of the Internet at the beginning of the 1990s incited a vibrant debate on the feasibility and desirability to regulate individuals’ actions online. Initially the Internet was perceived as unregulable from two aspects; firstly, it was considered that its design characteristics prevent attempts of external regulation; and secondly, that the traditional State regulation, based on the notion of territorial sovereignty, cannot be enforced nor function in cyberspace. From the first aspect stems the idea that from a technical perspective the Internet is inherently unregulable, due to its innate ability to resist regulation. The second reflects a modest version of cyber-libertarianism suggesting that the peculiarities of the Internet render State regulation inadequate. The question over the “regulability” of the Internet became crucial, as it progressively increased its population coverage. Nowadays, the question of regulability remains remarkably relevant, especially as the transition from IPv4 to IPv6 gives new impetus to the discussion of Internet Governance. This article addresses regulability of the Internet under the light of the new features IPv6 will introduce, focusing primarily on anonymity. It aims to prove that anonymity – usually cited as a main reason why the Internet is unregulable, or resistant to State regulation – is only the result of specific protocol design choices made during Internet’s infancy, and will be less common under the new Internet Protocol. It concludes that there is no valid ground anymore to argue that the Internet is inherently unregulable, while the significant limitation of anonymity will allow better State regulation.